INFLUENCE OF SOCIAL MEDIA ON CROSS CULTURE COMMUNICATION AMONG YOUNG ADULTS - Kukuh Satria; Dimah Azahra; Salsa Sabilla Alin Safitri; Zami Aqil Alkhobir; Nargis (Media Inovasi Pendidikan dan Publikasi, 2025)
This study explores the influence of social media on cross-cultural communication among young adults, emphasizing its role in shaping cultural awareness, empathy, and identity. By analyzing data collected through questionnaires and semi-structured interviews with Indonesian young adults aged 18–30, the study uncovers the dual impact of social media. Platforms such as Instagram and TikTok are identified as key facilitators of cultural exchange, fostering understanding and reducing stereotypes through engaging multimedia content. Participants reported enhanced cultural awareness and empathy, often discovering new traditions and norms while gaining appreciation for their cultural heritage. However, challenges such as language barriers, misinterpretations, and stereotyping highlight the need for improved digital literacy. Employing a qualitative approach and thematic analysis, the study underscores the transformative potential of social media in bridging cultural divides. These findings suggest that responsible and informed use of social media can amplify its capacity as a medium for intercultural dialogue and mutual understanding.